Kebijakan Pemerintah Daerah Dalam Peningkatan Kesejahteraan Buruh Sawit - Muhammad Novan Prasetya; Agus Nisfur Romdini; Aenal Fuad Adam (SOCIETAS, 2024)
The development of the palm oil industry in Papua, especially in Merauke Regency, has had a major impact on workers' welfare. Although palm oil production continues to increase, conditions for palm oil workers are often inadequate, including low wages, job uncertainty, and a lack of job protection. Even though there are sustainability certification efforts such as ISPO, many labor rights violations still occur. The importance of worker protection is recognized internationally through the United Nations Guiding Principles on Business and Human Rights (UNGP BHR). However, its implementation is still less than optimal in the field. Solutions to improve the welfare of palm oil workers involve collaboration between workers, government and companies. This includes the formation of strong labor unions, the implementation of labor-oriented CSR policies, and increased government regulations regarding minimum wages and job protection. Synergy between the three parties is needed to achieve better worker welfare in the Papuan palm oil industry, especially in Merauke Regency